Character Development of Peter in J.M Barrie "Peter and Wendy" Novel - Munti, Ayu Haritsa; Valiantien, Nita Maya; Dewi Max, Jonathan irene Sartika (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
Character development is the transformation process of the character from bad character to good character or the opposite that influenced by intrinsic elements. That is why the researchersused the guide from intrinsic elements and used the structuralism theory from Seymor Chatman. In this research, the researchers focused on the development of Peter, the main character. The researchers also used characterization theory from Rimmon Kenan to characterized Peter. This research used qualitative content analysis as the research design. The result of the research showed that even though many says that Peter is a flat character that impossible to change, the researcher found that the influence of Wendy towards Peter, she changed him into a better version of himself, appreciated the lost boys, and even though his thought about parents was not good, he still let the lost boys to leave and have their own parents. The researchersalso found influence of intrinsic elements on Peter’s character development. First, plot showed his condition from the beginning until the ending events. Second, setting showed his background in Neverland, the place where he lived.